2018
DOI: 10.1093/annonc/mdy151.097
|View full text |Cite
|
Sign up to set email alerts
|

Treatment patterns and costs of care for patients diagnosed with hepatocellular carcinoma (HCC) in the United States (U.S.)

Abstract: Methods: 12 patients (8 men, 4 women) with a median age of 64.5 years [range 44-83] suffering from both liver cirrhosis B7-B9 and unresectable nonmetastatic HCC were treated once or twice with Y-90 resin microspheres in our hospital in the years 2013-2017. In most patients alcohol abuse was the cause of liver cirrhosis. TACE was considered not to be effective in these patients. Our exclusion criteria for selective internal radiotherapy (SIRT) were either serum bilirubin >2.4 mg%, infiltration of the portal v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 0 publications
0
8
0
Order By: Relevance
“…A total of seven studies reported mean per month direct medical costs [ 52 , 57 , 65 , 68 , 71 , 74 , 103 ]; two of these studies described only patients receiving systemic treatment [ 52 , 57 ] and one compared costs among patients with HCV and cirrhosis, HCC or transplant [ 103 ]. The remaining four studies described monthly costs among nonselected cohorts ( Supplementary Table 5 ) [ 65 , 68 , 71 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…A total of seven studies reported mean per month direct medical costs [ 52 , 57 , 65 , 68 , 71 , 74 , 103 ]; two of these studies described only patients receiving systemic treatment [ 52 , 57 ] and one compared costs among patients with HCV and cirrhosis, HCC or transplant [ 103 ]. The remaining four studies described monthly costs among nonselected cohorts ( Supplementary Table 5 ) [ 65 , 68 , 71 , 74 ].…”
Section: Resultsmentioning
confidence: 99%
“…A total of 16 studies reported long-term direct medical costs [ 17 , 39 , 43 , 44 , 46 , 49 , 50 , 53 , 56 , 57 , 60 , 61 , 70 , 71 , 81 , 104 ]; three of these studies described charges [ 17 , 56 , 104 ], four described costs related to specific interventions [ 53 , 57 , 61 , 81 ] and five described costs among specific etiologies [ 39 , 43 , 44 , 46 , 49 ]. The remaining four studies described long-term costs among nonselected cohorts ( Supplementary Table 6 ) [ 50 , 60 , 70 , 71 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…HCC emerges primarily in older adults [29]. In addition to the underlying HCC etiology, older adults with HCC are likely to have additional co-morbidities such as cardiovascular or pulmonary disease [30], and it is not uncommon for patients with HCC to have multiple co-morbidities [31]. Liver cirrhosis, with compromised liver function and decreased hepatic reserve, is a major risk factor for HCC development.…”
Section: Co-morbiditiesmentioning
confidence: 99%
“…Although there are several studies in which the treatment patterns and/or healthcare costs of patients diagnosed with any stage or advanced stages of HCC have been evaluated in real-world settings [3,[9][10][11][12][13][14][15], there is limited information available regarding the real-world treatment patterns and healthcare economic burden specifically of patients diagnosed with locoregional disease, especially in USA. In the multi-national BRIDGE Study, Park et al reported that TACE, which was the most commonly used first-line therapy across patients with any stage HCC, was received by a third of patients in North America 2005-2012 (n = 2326; 37% had stage 0-A; 10% had stage B; 53% had stage C or D) [3].…”
mentioning
confidence: 99%